ASPECTS OF REGULATORY BILYET GIRO IN INDONESIAN CIVIL LAW - Eva Dwi Nur Aini; Safiratul Ummah; Sumriyah (Media Inovasi Pendidikan dan Publikasi, 2023)
Along with the rapid development of technology, it also has a significant impact on all aspects of human life. Including changes in the payment system in Indonesia, which previously only used cash as a legal means of payment, but now everyone can easily make payments to anyone using non-cash payments. As we know, people are more interested in fast, effective and efficient payments. Of course, payment using a giro is one of them. As is well known, a giro is an order for transfer from the withdrawal's current account to the recipient's current account, so payments cannot be made in cash. The main problem that is the focus is the demand deposit slip which cannot be transferred to a third party, because the demand deposit slip does not contain a clause related to how it is transferred.